Qos Analysis In The Application Of HTB At Computer Laboratory Of Engineering Faculty Of Universitas Muhammadiyah Bengkulu - Rahmadhan, Ihsan; Khairil, Khairil; Akbar, Abdussalam Al (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
Bandwidth management is needed therefore the existing bandwidth is divided according to the needs of each connected connection. One method that can stabilize the distribution of bandwidth is the Hierarchical Token Bucket (HTB) method. This study aims to adjust the amount of bandwidth to suit the needs of internet usage for each user without making one user dominate the use of bandwidth on the internet network. The research was conducted in 5 stages, namely: problem analysis, data collection, HTB design and implementation, HTB implementation and analysis of the final results of the system with HTB. Problem analysis and data collection are obtained through direct observation and observation. Design and implementation are done with the HTB method on the proxy router. The HTB method allows us to make the queue more structured, by doing multilevel groupings. The test results show that the HTB method can manage bandwidth usage for each user when using the internet simultaneously. From the analysis of the application of the HTB method in the computer laboratory of engineering faculty in Universitas Muhammadiyah Bengkulu, it shows that loyal users get bandwidth based on their limit-at and priority, which is equal to